Unbundling Efficient Breach: An Experiment - Maria Bigoni; Stefania Bortolotti; Francesco Parisi; Ariel Porat (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2016)
Current law and economics scholarship analyzes efficient breach cases monolithically. The standard analysis holds that breach is efficient when performance of a contract generates a negative total surplus for the parties. However, by simplistically grouping efficient breach cases as of a single kind, the prior literature overlooks that gainseeking breaches might be different from loss-avoiding breaches. To capture these different motives, we designed a novel game called Contract-Breach Game where we exogenously varied the reasons for the breach — pursuing a gain or avoiding a loss — under a specific performance remedy. Results from an incentivized laboratory experiment indicate that the motives behind the breach induce sizable differences in behavior; subjects are less willing to renegotiate when facing gain-seeking than loss-avoiding breaches, and the compensation premium obtained by the promisee is higher. Our analysis suggests that inequality aversion is an important driver of our results; indeed, inequality-averse subjects accept low offers more often in cases of loss-avoiding breaches than gain-seeking breaches. These results give us insight into the preferences and expectations of ordinary people in a case of a breach.
Keywords: K12; D86; C9; 330